The effects of the eddy-induced advection coefficient in a coarse-resolution coupled climate model - Farneti, Riccardo (author); Gent, Peter (author) (Ocean Modelling, 2011)
The role of the eddy-induced advection coefficient κ, used in the Gent and McWilliams (1990) parameterisation (GM), is analysed in terms of the response to idealised wind stress perturbation experiments in the GFDL global coupled climate model CM2.1, and compared to solutions with an eddy-permitting version of the same coupled model, CM2.4. The closure implemented in CM2.1 for K is flow-dependent and includes a maximum limit that caps its value. In this paper, we present simulations with a modified version of CM2.1, where the upper limit for K is doubled to 1200 m² s⁻¹ and the cap to the isopycnal slope Smax in GM is also increased to 1/100 from 1/500. These changes allow their product, K Smax, which is the upper limit to the effect of parameterised eddies, to be an order of magnitude higher than in the original CM2.1 version. Modifications to both GM parameters result in changes in the mean circulation and overall climatology that are non-negligible, which shows that attention has to be paid to the GM implementation during model development. Increasing the value of K does produce a stronger compensation between mean and eddy-induced meridional overturning circulations under stronger wind stress forcing, but the residual circulation response is still stronger than in the eddy-permitting model CM2.4. We show that spatially varying K, both in the horizontal and vertical directions, is necessary for a correct simulation of the response to changes in the wind stress. New and improved closures for K are needed, and should be tested in coupled climate models.